Ideologi Welfare State dalam Dasar Negara Indonesia: Analisis Putusan Mahkamah Konstitusi Terkait Sistem Jaminan Sosial Nasional - Alfitri Alfitri (The Constitutional Court of the Republic of Indonesia, 2016)
Are the objective of Indonesia “promoting the general welfare”, and the fifth principle of Pancasila “social justice for all people of Indonesia”, as well as the constitutional mandate to hold a social security system must be expressed in terms of the state positions itself to be responsible for ensuring a decent standard of living for all citizens? This paper will analyze whether the interpretation of welfare state ideology of the government in the Act No. 40/2004 on National Social Security System had violated the 1945 Constitution. This paper supports the argument of the Constitutional Court holding that social insurance programs adopted by the government meet the constitutional criteria. The existence of the constitutional criteria makesthe welfare state ideology of Indonesia open to interpretation, and this argument is more appropriate to the context and realistic about the ability of Indonesia to provide social security for its citizens.